Metaverse applications in architecture as a tool for achieving sustainability - Mohamed Mohamed; Amir Elmahdy; Abdullah Mohammed (JES: Journal of Engineering Sciences, 2025)
Buildings are the largest sector contributors of greenhouse gas global emissions, highlighting a critical need for innovative sustainable solutions. This research explores the potential of the metaverse in enhancing architectural building sustainability. The research objectives are (1) identify the key metaverse applications across the building lifecycle, (2) explore the potential of the metaverse in sustainable architectural practices, and (3) highlight architectural examples that demonstrate the impact of the metaverse on sustainability contributions. A systematic literature review of 22 publications shows key trends and insights in the selected studies. Content analysis indicates that the metaverse provides significant benefits across the building lifecycle. We identify key metaverse tools supporting sustainable architecture practices, such as ecological assessment, that visualize architectural concepts in a virtual simulated environment, making architectural design more efficient for sustainability. The metaverse improves team collaboration and helps make analytical decisions. Digital twins (DT) are used to manage buildings by integrating Internet of Things (IoT) sensors into buildings. The metaverse also offers a transformative tool for preserving the heritage buildings and facilitating their reuse. These applications improve sustainable architectural practices and minimize the environmental impact of the buildings. Yet, the metaverse remains confronted with challenges such as the need for high-speed network connections, initial expenses for software and hardware, and the need for government regulation policies to be addressed. The research presents architectural examples that demonstrate the applications of the metaverse, highlighting their role in enhancing operational efficiency, reducing energy consumption, enabling predictive maintenance, and supporting the preservation of cultural heritage.